2009
DOI: 10.1097/pas.0b013e3181ac675b
|View full text |Cite
|
Sign up to set email alerts
|

KIT is an Independent Prognostic Marker for Pancreatic Endocrine Tumors

Abstract: Prediction of the biologic behavior of pancreatic endocrine tumor (PET) without local invasion or metastasis is often difficult. The 2004 World Health Organization (WHO) classification uses size, angioinvasion, mitotic activity, and Ki-67 index as prognostic criteria. Recently, cytokeratin 19 (CK19) was shown to be another prognostic marker, but the mechanism by which CK19 predicts prognosis is unknown. As CK19 is the first cytokeratin expressed in all epithelial cells in fetal pancreas, we sought to test expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…This latter feature showed a significant association with tumour aggressiveness and patients’ shorter survival at univariate analysis ( P < 0.001), which was not retained at multivariate analysis. This result differs from that by Zhang et al [33] who reported that KIT expression was an independent prognostic factor. Concerning EGFR and HER2, neoplastic cells stained for EGFR in 13% (18/140) and for HER2 in 2% (3/140) of samples.…”
Section: Discussioncontrasting
confidence: 99%
“…This latter feature showed a significant association with tumour aggressiveness and patients’ shorter survival at univariate analysis ( P < 0.001), which was not retained at multivariate analysis. This result differs from that by Zhang et al [33] who reported that KIT expression was an independent prognostic factor. Concerning EGFR and HER2, neoplastic cells stained for EGFR in 13% (18/140) and for HER2 in 2% (3/140) of samples.…”
Section: Discussioncontrasting
confidence: 99%
“…NETs can also be further subdivided into three subgroups, G1/G2/G3, according to their mitotic index and Ki-67 index. Notably, the biological features of pNENs have been well researched, and the Ki-67 proliferation index as well as CK19 12 , p27 13 , and KIT 14 expression in the tumour cells have been identified as important predictive factors. However, these characteristics are not always a reliable reflection of treatment effectiveness or patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…While earlier papers showed inconsistent results (Fjallskog et al 2003, Koch et al 2006, in more recent studies, a prognostic role for c-KIT has been highlighted. Zhang et al (2009) reported that immunostaining for c-KIT is a significant independent factor associated with poor prognosis in a series of 97 PETs. Corbo et al (2012) analysed a series of 140 PETs and found no mutations of EGFR, HER2 and PDGFRa (PDGFRA), while KIT was mutated in only one case.…”
Section: Alteration Of Growth Factors and Receptorsmentioning
confidence: 99%